Structural and biochemical assessment of the molecular binding of hexylresorcinol to insect immune phenoloxidase: A quest for a new insecticidal activity. Issue 4 (19th April 2022) - Aloui, Sarra; Ghazouani, Tesnime; Raboudi, Faten; Talbi, Wafa; Vanden Broeck, Jozef; Salghi, Rachid; Fattouch, Sami
Abstract: The enzyme phenoloxidase (PO) plays an essential role in insect immune defense. Phenolic compounds sharing structural homology with PO substrates could act as substrate analogues, and may interfere with insect physiological process, thus, leading to their control. Herein, the bioinformatic molecular docking was used to predict the interaction of the crystal 3D structure of the insect Manduca sexta PO (PDB: 3HHS) with the antiseptic 4 hexylresorcinol (4‐Hr). The method was firstly validated using phenylthiourea (PTU) as reference ligand. Data demonstrated the ability of the 4‐Hr to bind to M. sexta PO with binding energy score ΔG = −372, 285 Kcal/mol indicative of a plausible affinity to active site of the enzyme, nevertheless, the affinity of PTU was stronger with a binding energy of ΔG = −462.173 Kcal/mol. Furthermore, biochemical in vitro assays confirmed the behavior of 4‐Hr as substrate‐analog when binding to the active site of the insect PO leading to its competitive inhibition. This is the first report demonstrating the molecular bases of the usefulness of hexylresorcinol as a promising insecticide. Further investigations could emphasize synergistic effects of 4‐Hr with other insecticides in integrated pest management (IPM) programs.